The Role of Strategic Transformation in the University Education Management - Sharif, Bakhtiar Aubaid; Kaka Mala, Hoshiar Marouf; Ali, Noor Azman (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Objective: The purpose of this study was to investigate the role of strategic transformation in university education management. Methodology: This research is a descriptive-correlation study. The statistical population of this study consists of all leaders and academic staff in polytechnic universities in the Kurdistan Region of Iraq who were selected by available sampling method using Morgan sample size formula. A questionnaire consisting of (34) items was designed to collect data on the field side, where 500 questionnaires were distributed to university leaders and lecturers in polytechnic universities (Erbil, Sulaimani, Duhok). 440 questionnaires were returned for analysis. In this study a standard questionnaire was used to measure variables. All statistical analyzes were performed with SPSS software version 23. Results: The results showed that strategic change had a significant effect on education management. Conclusion: The most important conclusions were that the existence of a positive moral relationship between the strategic transformation and university education management in polytechnic universities in the Kurdistan Region of Iraq.